2019
DOI: 10.1097/md.0000000000016350
|View full text |Cite
|
Sign up to set email alerts
|

Automatic current selection with iterative reconstruction reduces effective dose to less than 1 mSv in low-dose chest computed tomography in persons with normal BMI

Abstract: Most of the recent studies have used fixed tube current while few investigators use automatic current selection (ACS) with iterative reconstruction (IR) techniques to reduce effective dose (ED) to < 1 mSv in low-dose chest computed tomography (LDCCT). We investigated whether image quality of lungs as produced by a fixed tube current (FTC) of 35 mAs can be maintained with ED < 1 mSv produced by ACS with IR techniques in LDCCT. A total of 32 participants were included. The LDCCT was performed by a FTC 35 mAs (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, we used a fixed tube current and therefore, the radiation dose was not adjusted to the individual patient. Recently, Chen et al (22) successfully performed ULD chest CT using automatic tube current modulation, but they included only patients with normal range BMIs (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we used a fixed tube current and therefore, the radiation dose was not adjusted to the individual patient. Recently, Chen et al (22) successfully performed ULD chest CT using automatic tube current modulation, but they included only patients with normal range BMIs (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al. (22) successfully performed ULD chest CT using automatic tube current modulation, but they included only patients with normal range BMIs (22).…”
Section: Discussionmentioning
confidence: 99%
“…With MA‐PET, the radiation dose could be lowered by factor 10 compared to a standard whole‐body PET/CT 15 . As a result, a moderate radiation exposure similar to a low‐dose‐CT of the chest could be accomplished 16 . Even the combination of initial standard PET/CT and supplemental minimal‐activity PET/CT is in the accepted range of equivalent doses for single PET scans.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that automatic current selection setup was more effective than the fix tube current according to the ALARA principle. These findings suggest that the automatic current selection with iterative reconstruction technique can reduce the effective dose to an average of 0.71 mSv (reduction of radiation dose by ~50%), whereas it can maintain an image quality comparable to that obtained with the fixed-tube-current of 35 mAs with iterative reconstruction technique in individuals with a normal body mass index ( 52 ). It is noteworthy that different organs have different risks of radiation-induced cancer.…”
Section: Specific Recommendations and Measures For Reducing X-ray Rad...mentioning
confidence: 94%